If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 43 + n = 49 Solving 43 + n = 49 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + -43 + n = 49 + -43 Combine like terms: 43 + -43 = 0 0 + n = 49 + -43 n = 49 + -43 Combine like terms: 49 + -43 = 6 n = 6 Simplifying n = 6
| E+29=36 | | 16+p=38 | | x^2+12x+4320=0 | | 34-x=18 | | 27+f=35 | | 2/7(2x+5/7)=9/154 | | 2x+7=9/4 | | 21-a=7 | | 83-7x=11x+15 | | 21+n=49 | | 4x-20=-5/2 | | 16+r=40 | | s-32=9 | | 3b+(-6)=-12 | | 0.5=42/(36+x) | | h=-10x^2-27x+5 | | 42+x=56 | | y=1/4*x^2-x-7 | | 8.7b-0.4=17 | | 7-3x+8+2x-2=8+2*5 | | N-24=31 | | 4x+64+45=7/2 | | 27-p=3 | | 8/10=a/6 | | (a/b)=10a | | 2.2r+0.47=1.79 | | T+22=57 | | 43=6.2x+2.4x | | j/9-9=5/6 | | 0.13y-0.6=0.83 | | M-21=34 | | 5y-19=2(y-5) |